2011
DOI: 10.1002/jmri.22828
|View full text |Cite
|
Sign up to set email alerts
|

Gadoxetic acid‐enhanced MRI findings of early hepatocellular carcinoma as defined by new histologic criteria

Abstract: Purpose: To describe the imaging features of early hepatocellular carcinoma (HCC) on gadoxetic acid-enhanced MRI (Gd-EOB-MRI) in comparison with multidetector computed tomography (MDCT) examinations. Materials and Methods:We analyzed imaging findings of 19 pathologically proven early HCC lesions in 15 patients who underwent both MDCT and Gd-EOB-MRI at 3.0 Tesla (T) units before surgery. MRI included in-phase and outof-phase T1-weighted dual-echo gradient-recalled-echo sequences, dynamic T1-weighted images befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
0
37
1
1
Order By: Relevance
“…Since early HCCs show incomplete neoangiogenesis, isoattenuation on vascular phases is frequently seen in approximately 44% of early HCCs on multiphasic CT images [59]. However, because OATP8 expression decreases during hepatocarcinogenesis prior to complete neoangiogenesis and increased arterial flow, borderline hepatic nodules can be seen as nonhypervascular and hypointense nodules on HBP [80,81,82]. On Gd-EOB-DTPA-enhanced MRI, a considerable number of early HCCs, and some HGDNs, are hypointense on HBP [78] due to underexpression of OATP (Fig.…”
Section: Imaging-based Characterization Of Borderline Hepatic Nodulesmentioning
confidence: 99%
“…Since early HCCs show incomplete neoangiogenesis, isoattenuation on vascular phases is frequently seen in approximately 44% of early HCCs on multiphasic CT images [59]. However, because OATP8 expression decreases during hepatocarcinogenesis prior to complete neoangiogenesis and increased arterial flow, borderline hepatic nodules can be seen as nonhypervascular and hypointense nodules on HBP [80,81,82]. On Gd-EOB-DTPA-enhanced MRI, a considerable number of early HCCs, and some HGDNs, are hypointense on HBP [78] due to underexpression of OATP (Fig.…”
Section: Imaging-based Characterization Of Borderline Hepatic Nodulesmentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…Thus, in addition to the enhancement pattern, more information is needed to diagnose indeterminate nodules. Hepatocyte-specific contrast agents (so-called dual functional agents) may provide additional functional information that can improve the detection and characterization of HCCs [103][104][105][106][107][108][109][110].…”
Section: Mri Using New Contrast Mediamentioning
confidence: 99%